Human dignity and biomedical ethics from a Christian theological perspective - Körtner, Ulrich H. J. (HTS teologiese studies, 2011)
The argument of human dignity plays an important role in current debates on human rights and their relevance in modern biomedicine. When discussing the contribution of Christian theology to current debates on human dignity and human rights the thesis is not that the modern idea of human dignity depends on a theological grounding. Also, it is not the task of theology to legitimate rights as Christian a posteriori. We do not need to deduce modern human rights from theological doctrines. The theological challenge is to find an access for Christians from their belief to the modern idea of human rights and human dignity and to discuss the contribution which theology and the churches can make to further development of human rights. The Christian image of man, which serves as the foundation for the church position on bioethical topics in the German-speaking context, is a mix of biblical motives, a Kantian interpretation of the concept of human dignity and an interpretation of the German constitutional law inspired by the Catholic tradition of natural law. The following presented theological understanding of human dignity, in contrast, was inspired by the insights of the Pauline doctrine of justification and its Protestant reinterpretation.